Impact of post-admission changes in potentially inappropriate medication use on risk of subsequent hospitalization among nursing home residents - Zhao, Jing; Chae, Hyunwoo; Ah, Young-Mi; Jun, Kwanghee; Lee, Ju-Yeun (Frontiers in Pharmacology, 2025)
ObjectivesAs the population of nursing home (NH) residents grows, the management of polypharmacy and potentially inappropriate medications (PIMs) becomes crucial. Limited research exists on how changes in PIM use affect adverse outcomes, or the benefits of reducing such medications. This study explores post-admission trajectory of PIM utilization and polypharmacy, and their association with hospitalization risk.MethodsAnalyzing national claims data from 23,982 seniors aged ≥65 admitted to NHs from 2008 to 2018, we assessed PIM utilization based on the 2019 Beers criteria and calculated the total number of medications prescribed during the first month of each quarter in the year following NH admission. We then used a cause-specific hazard model to explore how changes in the number of medications and PIM use were associated with the risk of hospitalization in the following 2 months.ResultsPost-admission, medication and PIM use increased notably, especially in the first month, with 26% and 34% of residents experiencing increases, respectively. Deprescribing peaked in the second quarter, with 21% of residents reducing their medication use and 25% reducing PIM use. Residents with escalations in medication usage faced a 61% higher risk of hospitalization by the final quarter, while those reducing their medication count had a 21% lower risk by the second quarter. Increases in PIM use were linked to higher hospitalization risks (Quarter 1 (Q1): aHR 1.55 [1.38–1.75], Q4: aHR 1.80 [1.48–2.19]). Conversely, reductions in such use did not significantly alter hospitalization risk.ConclusionThese findings underscore the need for targeted interventions to manage polypharmacy and PIM use effectively in this population.